2021
DOI: 10.1155/2021/6686964
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic J-Pouch Perforation following a Blunt Abdominal Injury

Abstract: A 46-year-old male was admitted to the trauma department after a motor vehicle accident. He presented with severe abdominal pain and a distended abdomen with peritonitis. His past surgical history included total proctocolectomy with ileal J-pouch anal anastomosis for ulcerative colitis 20 years previously. Computed tomography showed free peritoneal air and fluid in the abdomen mandating an exploratory laparotomy. A perforation at the ileal J-pouch blind end was found. Primary closure with diverting loop ileost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Several reports of ileal pouch perforation have been reported in the literature, all of which are listed below [ 11 – 20 ] (Table 1 ). Hsu and Leonid et al reported perforation of the ileal pouch due to external factors, such as blunt trauma [ 11 , 12 ]. In pregnant women with an enlarged uterus, increased pouch pressure associated with perforation in relation to adhesions were reported [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports of ileal pouch perforation have been reported in the literature, all of which are listed below [ 11 – 20 ] (Table 1 ). Hsu and Leonid et al reported perforation of the ileal pouch due to external factors, such as blunt trauma [ 11 , 12 ]. In pregnant women with an enlarged uterus, increased pouch pressure associated with perforation in relation to adhesions were reported [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%